The Combined Use of in Silico, in Vitro, and in Vivo Analyses to Assess Anti-cancerous Potential of a Bioactive Compound from Cyanobacterium Nostoc sp. MGL001 - Niveshika,; Verma, Ekta; Maurya, Shashank K.; Mishra, Rajnikant; Mishra, Arun K. (Frontiers in Pharmacology, 2017)
Escalating incidences of cancer, especially in developed and developing countries, demand evaluation of potential unexplored natural drug resources. Here, anticancer potential of 9-Ethyliminomethyl-12-(morpholin-4- ylmethoxy) -5, 8, 13, 16 – tetraaza – hexacene - 2, 3- dicarboxylic acid (EMTAHDCA) isolated from fresh water cyanobacterium Nostoc sp. MGL001 was screened through in silico, in vitro, and in vivo studies. For in silico analysis, EMTAHDCA was selected as ligand and eleven cancer related proteins (Protein Data Bank ID: 1BIX, 1NOW, 1TE6, 2RCW, 2UVL, 2VCJ, 3CRY, 3HQU, 3NMQ, 5P21, and 4B7P) which are common targets of various anticancer drugs were selected as receptors. The results obtained from in silico analysis showed that EMTAHDCA has strong binding affinity for all the eleven target protein receptors. The ability of EMTAHDCA to bind active sites of cancer protein targets indicated that it is functionally similar to commercially available anticancer drugs. For assessing cellular metabolic activities, in vitro studies were performed by using calorimetric assay viz. 3- (4, 5-dimethylthiazol- 2-yl)-2, 5 diphenyltetrazolium bromide (MTT). Results showed that EMTAHDCA induced significant cytotoxic response against Dalton’s lymphoma ascites (DLA) cells in a dose and time dependent manner with an inhibitory concentration (IC50) value of 372.4 ng/mL after 24 hours of incubation. However, in case of normal bone marrow cells, the EMTAHDCA did not induce cytotoxicity as the IC50 value was not obtained even with higher dose of 1000 ng/mL EMTAHDCA. Further, in vivo studies revealed that the median life span/survival days of tumor bearing mice treated with EMTAHDCA increased significantly with a fold change of approximately 1.9 and 1.81 corresponding to doses of 5 and 10 mg/kg body weight (B.W.) of EMTAHDCA respectively, as compared to the DL group. Our results suggest that 5 mg/kg B.W. is effective since the dose of 10 mg/kg B.W. did not show any significant difference as compared to 5 mg/kg B.W. Taken together, our findings based on in silico, in vitro, and in vivo analyses suggest that EMTAHDCA has potential anticancer effects, and thus, can be considered for cancer treatment.